Exploring Project Risk Management Practices of Ghanaian Building Contractors. - Boateng Okyere Wilson (KNUST, 2025)
A thesis submitted to the Department of Construction Technology and Management, College of Art and Built Environment in partial fulfilment of the requirement for the Degree of Master of Science November, 2018.